Effect of silica coating and silane surface treatment on the bond strength of soft denture liner to denture base material (Journal of Applied Oral Science, 2013)
OBJECTIVE: This study investigated the effects of different surface treatments on the tensile bond strength of an autopolymerizing silicone denture liner to a denture base material after thermocycling. MATERIAL AND METHODS: Fifty rectangular heat-polymerized acrylic resin (QC-20) specimens consisting of a set of 2 acrylic blocks were used in the tensile test. Specimens were divided into 5 test groups (n=10) according to the bonding surface treatment as follows: Group A, adhesive treatment (Ufi Gel P adhesive) (control); Group S, sandblasting using 50-µm Al2O3; Group SCSIL, silica coating using 30-µm Al2O3 modified by silica and silanized with silane agent (CoJet System); Group SCA, silica coating and adhesive application; Group SCSILA, silica coating, silane and adhesive treatment. The 2 PMMA blocks were placed into molds and the soft lining materials (Ufi Gel P) were packed into the space and polymerized. All specimens were thermocycled (5,000 cycles) before the tensile test. Bond strength data were analyzed using 1-way ANOVA and Duncan tests. Fracture surfaces were observed by scanning electron microscopy. X-ray photoelectron spectrometer (XPS) and Fourier Transform Infrared spectrometer (FTIR) analysis were used for the chemical analysis and a profilometer was used for the roughness of the sample surfaces. RESULTS: The highest bond strength test value was observed for Group A (1.35±0.13); the lowest value was for Group S (0.28±0.07) and Group SCSIL (0.34±0.03). Mixed and cohesive type failures were seen in Group A, SCA and SCSILA. Group S and SCSIL showed the least silicone integrations and the roughest surfaces. CONCLUSION: Sandblasting, silica coating and silane surface treatments of the denture base resin did not increase the bond strength of the silicone based soft liner. However, in this study, the chemical analysis and surface profilometer provided interesting insights about the bonding mechanism between the denture base resin and silicone soft liner.